PERAN MEDIA SOSIAL DALAM MEMBENTUK PERILAKU SOSIAL REMAJA - Zaki Salatin Amin Ginting; Wenti Susanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social media has become an important part of adolescents’ lives and plays a role in shaping patterns of social interaction, communication styles, and social behavior. This study aims to analyze the role of social media in shaping adolescent social behavior, both in positive and negative aspects. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation involving adolescents as key informants. The results show that social media contributes to improving communication access, expanding friendship networks, shaping self-identity, and increasing adolescent social participation. However, social media also contributes to individualistic behavior, self-comparison tendencies, reduced face-to-face interaction, and changes in communication patterns that are more digitally oriented. The intensity of use, self-control, as well as family and educational environments influence how social media shapes adolescent social behavior. This study concludes that social media has a dual role as a means of social development and a challenge in shaping adolescent social behavior.